Constructing Loyalty, Citizenship, and Identity: a Rhetorical History of the Japanese American Incarceration - (:unkn) unknown (My University, 2014)
This dissertation reexamines loyalty, citizenship, and identity in the United States by closely reading historical materials about the Japanese American incarceration. The Japanese American incarceration is a unique and important historical event for studying citizenship and identity, since it was a moment in the U.S. history that citizens of the country were incarcerated by their government. This raises a larger question beyond the incarceration. What does it mean to be a loyal American citizen? By closely analyzing texts generated by the U.S. government, the Japanese American community, and White American photographers, I identify multiple, conflicting meanings and implications behind the terms "loyalty," "citizenship," and "identity." I argue that American citizenship in moments of crisis is grounded in performance of Whiteness and loyalty to the country. In other words, racially marginalized American citizens are asked to prove their loyalty and assimilation to White culture in order to be judged as true American citizens. Democratic actions by targeted minority groups can be denied or silenced as inappropriate citizenship performance. This dissertation proposes two rhetorical strategies to counter misrepresented identity, loyalty, and citizenship of any minority groups. First, constructing two levels of collective identity, (1) a collective identity within a minority community and (2) a collective identity that can be shared with both the American public and the minority community, can challenge stereotypical understandings of the minority identity. In addition, dissociation of the implied connection between certain actions (e.g. military enrollment) and loyalty can also challenge a misrepresented minority identity. Second, visual representation of a blended identity as an American citizen who respects one's racial and cultural origin with smiles, innocence, and beauty would be a potential strategy to counter the dominant understanding of their identity, since these visual features would break a mental disconnection between the American public and the minority group.
Keywords: Citizenship; Identity; Japanese American; Loyalty; Race; Rhetorical History